Resolving the Inner Parsec of the Blazar J1924-2914 with the Event Horizon Telescope - Issaoun Sara (IOP Publishing Ltd, 2025)
The blazar J1924-2914 is a primary Event Horizon Telescope (EHT) calibrator for the Galactic center's black hole Sagittarius A*. Here we present the first total and linearly polarized intensity images of this source obtained with the unprecedented 20 mu as resolution of the EHT. J1924-2914 is a very compact flat-spectrum radio source with strong optical variability and polarization. In April 2017 the source was observed quasi-simultaneously with the EHT (April 5-11), the Global Millimeter VLBI Array (April 3), and the Very Long Baseline Array (April 28), giving a novel view of the source at four observing frequencies, 230, 86, 8.7, and 2.3 GHz. These observations probe jet properties from the subparsec to 100 pc scales. We combine the multifrequency images of J1924-2914 to study the source morphology. We find that the jet exhibits a characteristic bending, with a gradual clockwise rotation of the jet projected position angle of about 90 degrees between 2.3 and 230 GHz. Linearly polarized intensity images of J1924-2914 with the extremely fine resolution of the EHT provide evidence for ordered toroidal magnetic fields in the blazar compact core.